ВПЛИВ КОНЦЕНТРАЦІЇ CrB2 НА ФІЗИКО-МЕХАНІЧНІ ВЛАСТИВОСТІ КОМПОЗИТІВ FeCuNiSn ДЛЯ КАМЕНЕОБРОБНИХ ІНСТРУМЕНТІВ - Мечник, В.А.; Бондаренко, М.О.; Колодницький, В.М.; Ісонкін, О.М.; Коростишевський, Д.Л.; Пошванюк, Н.Ф. (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2020)
The effect of CrB2 powder addition on the mechanical (microhardness Н, modulus of elasticity Е) properties of composite materials based on iron, copper, nickel and tin sintered by cold pressing and subsequent vacuum hot pressing was studied. Initial powders had a dispersion of 5–50 µm. It is shown that increase in CrB2 amount leads to increase in hardness and elastic modulus. The wear rate decreases with an increase of CrB2 amount up to 2 wt. % and then increases. The values of material resistance to elastic fracture deformation (H/E) and resistance of material to plastic deformation (H3/E2) well correlate with the values of the wear resistance. The reasons of physico-mechanical and operational properties changes of sintered composite materials were discussed.